2021
DOI: 10.1039/d1sc01874d
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging and kinetic analysis of intermolecular polyoxometalate reactions

Abstract: We induce and study reactions of polyoxometalate (POM) molecules, [PW12O40]3− (Keggin) and [P2W18O62]6− (Wells–Dawson), at the single-molecule level, utilising TEM as an analytical tool, and nanotubes as test tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…1 nm, though note that terminal oxygen are not typically observed with TEM). Similar to their polyoxotungstate analogues, [54] the discrete species appeared to rapidly condense to larger nanoparticles during TEM observations, indicating that O atoms had dissociated from the POMs under the electron beam (Figure S1). Raman spectroscopy of PMo 12 @SWNT also provided strong evidence for POM encapsulation.…”
Section: Resultsmentioning
confidence: 91%
“…1 nm, though note that terminal oxygen are not typically observed with TEM). Similar to their polyoxotungstate analogues, [54] the discrete species appeared to rapidly condense to larger nanoparticles during TEM observations, indicating that O atoms had dissociated from the POMs under the electron beam (Figure S1). Raman spectroscopy of PMo 12 @SWNT also provided strong evidence for POM encapsulation.…”
Section: Resultsmentioning
confidence: 91%
“…Variable-temperature single-molecule atomic-resolution time-resolved electron microscopic (VT-SMART-EM) imaging is an emerging experimental tool for the study of kinetics and thermodynamics of individual chemical events ( 19 , 22 , 38 ), and it has provided direct experimental proof of the Rice–Ramsperger–Kassel–Marcus theory ( 39 ). In this study, we monitored several hundred individual events of the [2 + 2] reaction under VT/VV conditions at 103 to 493 K and 60 to 120 keV ( 10 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…These redox materials exhibit exceptional electrochemical stability. [70][71][72] We demonstrated that the formation of electron donor-acceptor systems composed of SWCNTs and encapsulated polyoxometalates is effective to modulate the interaction of inter-tubes, thus selectively extracting largediameter semiconducting SWCNTs. 73,74 The adaptability in chemical synthesis provides a wide variety of customized polyoxometalates with tunable redox potentials, which enables precise modulation of the electronic properties of SWCNTs.…”
Section: Introductionmentioning
confidence: 99%